Nutrition Evaluation Of Extrusion Products Made From Rice Milling Byproducts (Broken Rice And Rice Bran) - Rizal Syarief (Jurnal Teknologi dan Industri Pangan, 2000)
By products of of rice milling, especially broken rice and rice bran, are not commonly used as food product. The purpose of this research was to develop and analyzed the nutrition content of new extruded product made of mixed broken rice and rice bran. The hedonic values were analyzed to choose the best formulation. Nutrition component was analyzed by in vitro and in vivo method. Increasing the concentration of rice bran resulted in increase of the percentage of ash ( 1.29%-3.47%), fat (1.12%-3.11%), crude fiber (0.58%-2.09%), some of essential amino acid,FCE(17.18%-27.28%) and decrease of protein digesbility.